Effect of surfactants on the lightning breakdown voltage of palm oil and coconut oil based Al2O3nanofluids - Mohamad N.A.; Azis N.; Jasni J.; Ab. Kadir M.Z.A.; Yunus R.; Yaakub Z. (Institute of Physics Publishing, 2023)
Alumina; Aluminum oxide; Cationic surfactants; Electric breakdown; Lightning; Nanofluidics; Nanoparticles; Petroleum refining; Sodium dodecyl sulfate; Sulfur compounds; Breakdown patterns; Cetyltrimethylammonium bromide; Negative lightning; Negative polarity; Positive polarity; Sphere electrodes; Volume concentration; Volume percentage; Palm oil